Survival in the elderly after acute myocardial infarction: room for more improvement. - Mangion, Kenneth; Berry, Colin (Age & Ageing, 2014)
The authors reflect on the survival rate of elderly following an acute myocardial infarction (AMI). The authors state the higher risk of mortality in older persons with AMI as compared to younger patients due to the connection of increasing age with co-morbidity. The authors also mention the developments in health care for AMI patients and increase in prescription of an evidence-based medication to decrease the risk of AMI.